2020
DOI: 10.1016/j.ejmp.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Higher patient doses through X-ray imaging procedures

Abstract: Medical imaging using X-rays has been one of the most popular imaging modalities ever since the discovery of Xrays 125 years ago. With unquestionable benefits, concerns about radiation risks have frequently been raised. Computed tomography (CT) and fluoroscopic guided interventional procedures have the potential to impart higher radiation exposure to patients than radiographic examinations. Despite technological advances, there have been instances of increased doses per procedure mainly because of better diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 91 publications
0
12
0
2
Order By: Relevance
“…Based on the current hot topic debate about the significance of patient shielding, this review not only summarizes the evidence presented in the literature, but also puts it in the context of the technical developments in the same period [54][55][56][57]. In addition, non-dose-related aspects are considered in order to evaluate whether patient protection by means of contact shielding should be maintained or discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current hot topic debate about the significance of patient shielding, this review not only summarizes the evidence presented in the literature, but also puts it in the context of the technical developments in the same period [54][55][56][57]. In addition, non-dose-related aspects are considered in order to evaluate whether patient protection by means of contact shielding should be maintained or discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the development and widespread availability of cross-sectional imaging, in the last several decades, radiology has become pivotal in the diagnosis and management of many diseases. The use of medical imaging, including ionizing radiation-based modalities, continues to increase, raising concerns about patients’ radiation exposure, with reported cumulative effective doses exceeding 100 mSv for single procedures . Although accounting for only 17% of all medical examinations, multidetector computed tomography (CT) alone makes up approximately 50% of the total radiation burden for medical purposes, and a large multicenter trial by Rehani et al revealed that more than 1% of patients undergoing multiple CT examinations over 1 to 5 years received a cumulative effective dose above 100 mSv.…”
Section: Introductionmentioning
confidence: 99%
“…It is always a dilemma in all radiation practicing to balance the benefits against the risks. The article of M. Rehani and D. Nacouzi [15] highlights this problem emphasizing the concerns with the cumulative dose absorbed from multiple examination procedures. This requires focussing even more on dose minimizing technical solutions in the equipment, for instance with the recent development of the monochromatic X-ray sources, may be in the future also with the application of robotics.…”
Section: X-ray Dosimetry and Radioprotectionmentioning
confidence: 99%